The Effects of Demographic Change on GDP Growth: Research Focus on Russia - Goran Miladinov (Journal of World Economy, 2023)
There has been a downward trend in economic growth in several economies over the past few decades, with the slowdown trend particularly evident in the case of Russia. These records estimate how much of this growth slowdown can be accounted for by demographic changes. Specifically, this study estimated how a changing age structure of the population (between four groups-ages 0-14, 15-64, and 65+) has affected GDP growth using annual time series data for Russia. The analysis is applied using the Bayesian VAR model. The data for the study are obtained from the World Bank. It was found that demographic changes account for a significant portion of the downward trend in the economic growth of Russia during the past decade. Moreover, the continuation of the demographic shift toward an older population is likely a valuable factor that has increased GDP growth in Russia over the last couple of decades. The research results point out that during the last decade; demographic effects have not had any significant influence on the change of GDP growth levels in Russia. Therefore, the research study contributes in a way indicating that future growth of GDP in Russia will depend much more on the growth of structural productivity, new technologies and worker profitability and much less on demographic changes.